Agatha Christie Marple. They do it with mirrors [videorecording (DVD)] - Stone, Norman; Hickson, Joan, 1906-1998; Christie, Agatha, 1890-1976 (A & E Home Video ; Distributed by New Video, 2006)
Return to post-war England for mystery and a cup of tea. The consummate prim and proper crime-fighting spinster, Miss Jane Marple sets down her knitting needles to unwind the most ingenious crimes. As she travels from city to countryside and even the Bahamas, murders, missing bodies and haunted dreams have a habit of falling across Miss Marple's path.